Pembagian Waris Dengan Cara Bergilir Dalam Perspektif Kompilasi Hukum Islam - Hanik Latifah; Naachy, Dzin Nun (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2021)
Background. There is division of inheritance by way of rotation. Theprocedures for the implementation of inheritance by rotation need toexamining from the Compilation of Islamic Law.Aim. This study aims to the provisions of the Compilation of IslamicLaw in regulating the problems of inheritance and it implementation.Methods. The method used in this research is field research with aqualitative approach.Results. The procedure for implementing inheritance at the AttahdzibIslamic Boarding School is done by dividing the proceeds from theinheritance in rotation between one heir and another. Implementation inthis way is in accordance with the Compilation of Islamic Law article183, namely the distribution of the inheritance based on the agreementof the heirs after the heirs know their respective shares.